Mengeksplorasi Minat Dan Bakat Anak Usia Dini Melalui Permainan Edukasi - Hidupi, Dasa Wisra; Ningsih, Eva Marliah (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Early childhood is at a stage of rapid development that includes various aspects, such as physical, cognitive, emotional, and social. In this period of growth, their interests and talents become two fundamental elements that can be directed to maximize their potential. Interest refers to a child's propensity for a particular activity, while talent reflects an innate ability that can develop through practice and environmental support. One of the most efficient methods to optimize this exploration process is through educational games. Educational games in addition to acting as a means of entertainment, this game also functions as a learning tool that encourages creativity, critical thinking skills, social interaction, and the development of children's motor skills. The purpose of this article is to explore how educational games can be a medium for exploring early childhood interests and talents, based on theoretical analysis and the latest research studies. This study uses a qualitative method by reviewing relevant literature. This research resulted in the finding that educational play can provide great benefits in facilitating children's development by creating a fun, interactive, and holistic learning experience.